Legal Protection for Paylater Organizers in Bad Credit Using the Peer To Peer (P2p) Lending System - Asiyah, Siti Ayu; Alya'Labibah, Hanin (IHSA Institute, 2024)
Peer to Peer(p2p) lending is an online loan system in the financial services sector between loan recipients and lenders so that this system presents a pay later method which is the result of financial technology (fintech) in the financial services sector. The peer to peer (P2P) lending and borrowing process using the paylater method, even though it is done online, may result in legal consequences. The aim of this research is to find out how paylater credit is regulated using the peer to peer (p2p) lending system in society and to understand the legal protection that occurs if debtors face default or bad credit. The method used in this research is normative legal research using a statutory approach and a conceptual approach. The results of this research are that the legal protection that can be obtained by debtors is by using preventive and repressive legal protection, where later in this protection there are several stages of resolution that can be taken